BUREAUCRATIC BEHAVIOR MODEL IN POLICY IMPLEMENTATION TO ENHANCE EQUAL AND EXTENSIVE EDUCATION ACCESS (THE DEPARTMENT OF EDUCATION AND CULTURE GORONTALO DISTRICT) - Yacob Noho Nani, Asna Aneta, Zuchri Abdussamad, Rosman Ilato, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to define a bureaucratic behavior model in the implementation of the policies of enhancing equal and extensive education access to deliver educational services. To develop the behavior model, I hinge on the theory of behavior by Draha (1989), who describes bureaucratic behaviors as an interplay between individual and bureaucracy characters. This research brings into focus the development of a behavior model in public policy implementation.This research is carried out in the Department of Education and Culture Gorontalo District Gorontalo Province, one of the provinces in the eastern part of Indonesia. It is conducted using the qualitative descriptive method, and research informants are all employees involved in policy implementation in the research area. Two data types, i.e., primary (documents, photographs, and picture) and secondary (interview results and other research findings, and so forth), are used.Based on the results, there are several bureaucratic behavior factors which affect the enhancement of equal and extensive education access. The factors can be categorized into two, i.e., (a) behavior factors which boost successful policy implementation and (b) behavior factors which inhibit successful policy implementation to enhance equal and extensive education access.Predicated on the results, I develop a policy behavior model with three cardinal variables of bureaucratic behaviors. The three factors are (a) individuals’ characters within the organization, (b) bureaucratic characters, and (c) value characters in a bureaucracy culture. The interaction among the three characters is known as the Value Interaction Behavior (VIB).Using this model, it is expected that the mindset of bureaucratic behaviors, which is limited to be performance achievement-oriented, is changed to be a public-oriented one. Additionally, it is expected that the shift of ethical values can be manifested through turning the bureaucracy-oriented paradigm to be service-oriented by highlighting the values of openness, responsibility, and public accountability.